2022
DOI: 10.5811/westjem.2021.8.53063
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Triage Tool for Predicting Cardiac Arrest in the Emergency Department

Abstract: Background: Early recognition and prevention of in-hospital cardiac arrest (IHCA) have played an increasingly important role in the chain of survival. However, clinical tools for predicting IHCA are scarce, particularly in the emergency department (ED). We sought to estimate the incidence of ED-based IHCA and to develop and validate a novel triage tool, the Emergency Department In-hospital Cardiac Arrest Score (EDICAS), for predicting ED-based IHCA. Methods: In this retrospective cohort study we used electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Based on the SHAP analysis, we found that clinical variables associated with the occurrence of IHCA (i.e. oxygen supply and saturation, vital signs, and mental status) in previous studies were in line with variables that had a high influence on the output of the present model 32 34 . In addition to these key factors, our model included more clinical data such as medical history, symptoms, first aid, and hospital factors, increasing the predictive power over traditional statistical methods.…”
Section: Discussionsupporting
confidence: 71%
“…Based on the SHAP analysis, we found that clinical variables associated with the occurrence of IHCA (i.e. oxygen supply and saturation, vital signs, and mental status) in previous studies were in line with variables that had a high influence on the output of the present model 32 34 . In addition to these key factors, our model included more clinical data such as medical history, symptoms, first aid, and hospital factors, increasing the predictive power over traditional statistical methods.…”
Section: Discussionsupporting
confidence: 71%
“…Based on our previous data, 7 the AUROC of the model using the TTAS triage alone to predict hospital admission was 0.65. We further anticipated a difference of 0.075 in AUROC between the two triage methods.…”
Section: Methodsmentioning
confidence: 87%
“…Additionally, an electronic device is required to assist in triage evaluation. The TTAS also suffered from the same problem as the Emergency Severity Index (ESI), i.e., a large portion of undifferentiated Level 3 patients 7,8 . By contrast, physician gestalt perception, if carefully combined with some structured tools or data, might permit the defoliation of the many branches built into diagnostic trees 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of VSs monitoring in clinical practice is indisputable; however, it remains unclear which VS is more associated with the clinical risk of patients, at what interval VSs should be evaluated, and the best way to monitor them [6]. There are many studies in the literature examining the relationship between VSs measured at the time of presentation to the emergency department and mortality [23][24][25]. However, only a few studies have explored the relationship between VSs alone and hospitalization indications.…”
Section: Discussionmentioning
confidence: 99%